A NEW APPROACH ON THE TECTONOMETAMORPHIC MECHANISMS ASSOCIATED WITH P–T PATHS OF THE BARROVIAN-TYPE SILGARÁ FORMATION AT THE CENTRAL SANTANDER MASSIF, COLOMBIAN ANDES - Castellanos A., Óscar M.; Ríos R, Carlos A; Takasu, Akira (Earth Sciences Research Journal, 2008)
Metamorphic pressure and temperature trajectories are generally used as tools to interpret the tectonic history ofdeformed belts of rocks that record past activity along active plate margins. The pre-Devonian metamorphic sequenceof the Silgará Formation forms part of the ancient basement of the central Santander Massif, including pelitic schists, siliceous schists and intercalation of amphibolites accompanied by marble. This metasedimentary unit has been affected by Barrovian type metamorphism under middle-pressure/high-temperature conditions. This paper presents on the relationship of tectonic processes to pressure-temperature paths development.Detailed petrologic analysis of pelites and related rocks has been used to constrain the P-T history of this region in the eastern colombian cordillera. Mineral assemblages and Geothermobarometric calculations indicate metamorphic temperatures and pressures of 400-600 °C and 4.0-6.5 kbar, respectively.